2010
DOI: 10.1088/2041-8205/717/2/l118
|View full text |Cite
|
Sign up to set email alerts
|

GeV BREAKS IN BLAZARS AS A RESULT OF GAMMA-RAY ABSORPTION WITHIN THE BROAD-LINE REGION

Abstract: Spectra of the brightest blazars detected by the Fermi Gamma-ray Space Telescope Large Area Telescope cannot be described by a simple power law model. A much better description is obtained with a broken power law, with the break energies of a few GeV. We show here that the sharpness and the position of the breaks can be well reproduced by absorption of γ-rays via photon-photon pair production on He II Lyman recombination continuum and lines. This implies that the blazar zone lies inside the region of the highe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
267
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 238 publications
(277 citation statements)
references
References 27 publications
8
267
1
1
Order By: Relevance
“…Furthermore, Jorstad et al (2001Jorstad et al ( , 2010 found that γ-ray flares often occur after superluminal knots have separated away from the VLBI core. The results presented here support the inference that γ-ray emission still occurs parsecs downstream of the central engine, in contrast to conclusions based on theoretical arguments (e.g., Tavecchio et al 2010;Poutanen & Stern 2010). These arguments place the γ-ray emission zones within the broad-line region (BLR) at distances of < ∼ 1 pc from the central engine.…”
Section: Discussionsupporting
confidence: 73%
“…Furthermore, Jorstad et al (2001Jorstad et al ( , 2010 found that γ-ray flares often occur after superluminal knots have separated away from the VLBI core. The results presented here support the inference that γ-ray emission still occurs parsecs downstream of the central engine, in contrast to conclusions based on theoretical arguments (e.g., Tavecchio et al 2010;Poutanen & Stern 2010). These arguments place the γ-ray emission zones within the broad-line region (BLR) at distances of < ∼ 1 pc from the central engine.…”
Section: Discussionsupporting
confidence: 73%
“…less than one tenth of parsec (e.g. Finke & Dermer 2010;Ghisellini et al 2010;Poutanen & Stern 2010;Tavecchio et al 2010). In order to distinguish between the two hypotheses, we have followed the argument on the electrons cooling time as explained in Tavecchio et al (2010).…”
Section: Discussionmentioning
confidence: 99%
“…The spectral slope becomes steeper near a break energy of about several GeV. Qualitatively such details are well explained by pair-production opacity created by individual bright spectral lines and sharp spectral edges (Poutanen & Stern 2010;Stern & Poutanen 2014) in the far and extreme UV range. Such spectral details are naturally produced by the c 2016 RAS BLR responsible for the broad components of emission lines.…”
Section: Introductionmentioning
confidence: 87%
“…The spectra of FSRQ and bright (low-synchrotronpeak) BL Lacs obtained by the Large Area Telescope onboard of the Fermi Gamma-ray Space Telescope (Fermi/LAT) in the 0.1−30 GeV energy range reveal strong deviations from any smooth (single power-law or log-normal) spectral model (Abdo et al 2010;Poutanen & Stern 2010;Tanaka et al 2011;Stern & Poutanen 2011. Unlike the fainter BL Lac objects lacking observable disc and line emission, a nearly power-law spectrum observed in FSRQs in the 1 GeV range cannot be extrapolated to energies higher than several GeV.…”
Section: Introductionmentioning
confidence: 99%